Semen characteristics of pubertal yankasa rams fed zingiber officinale supplemented diets (2016)
Ginger (Zingiber officinale) is consumed by humans and has been reported to possess medicinal uses. It possesses androgenic property with significant increase on male reproductive parameters. This study assessed the reproductive performance of Yankasa rams fed diets supplemented with different levels of ginger powder. Ginger powder was added at 0,5,10,15 and20g/kg of the concentrate diet as T1, T2, T3, T4 and T5 respectively. Each treatment had five replicates while semen was collected once from all replicates in the treatments. Rams were fed experimental diets for 70 days. The parameters determined were: mass activity, motility, live: dead ratio, sperm volume, scrotal circumference and length. Mass activity values ranged from 0.67 in T5 to 3.00 in T3. However, there were significant increases in the mass activity of the ejaculate with increase in ginger inclusion up to T3 and subsequent reduction in T4 (1.33) and T5 (0.67). Similarly, scrotal length increased from 14.33cm in T1 to 16.33cm in T3, but decreased to 13.33cm in T5. No significant difference was observed in motility, liveability, volume of ejaculate and scrotal circumference, but numerical increases were obtained for motility, live: dead ratio, volume, sperm count and scrotal circumference. It can be concluded that ginger has positive effect on the improvement of semen quality of rams fed ginger powder supplement up to 10g/kg.